HARDWARE-SOFTWARE COMPLEX OF NAVIGATION SYSTEM FOR PRECISION FARMING - A. L. Trukhanovich; P. V. Kuchynski (Приборы и методы измерений, 2015)
The article presents a block diagram and operation of the algorithm of a hardware-software system developed for precision farming. An experimental model of hardware and software system is produced.